GROUNDWATER LEVEL FLOW MAPPING IN VICINITY OF PROPOSED JATIGEDE DAM - Yan Adhitya Wesda Wardhana; Heni Rengganis (Pusbindiklat - LIPI, 2012)
Jatigede Dam development that aims to tackle the water problems that exist in West Java of great importance.Positive impact arising from development of this Dam is rising shallow groundwater at the dug wells population.To prove this, needs to be monitoring of shallow groundwater in the area around the pool area will Jatigede Dam.This monitoring has been ongoing since the year 2008 up to this time, either during the rainy season and dryseason. This study aims to determine fluctuation of shallow groundwater in the wet season and dry before the damflooded, while also to know the flow of shallow groundwater through contour mapping shallow groundwater. Theresults obtained in the form of shallow ground water level fluctuations from 2008 through 2011, and map the flowof groundwater. Advance groundwater monitoring will be carried out until the reservoir is filled with water thatplanned in 2013.